Razvojna politika v OZN - Kunčič, Aljaž (Teorija in praksa, 2016)
This article critically assesses the dynamics of views on economic and social development within the United Nations (UN) and specialized international organizations through the lens of four development decades, the Human Development Index, and the Millennium Development Goals. Based on development results and prevalence in the literature, concepts for measuring human development and setting development goals involving a broad consensus and absence of ideology are found to be the most successful. It follows that a successful development policy must be eclectic and flexible, and that goals need to be few and easily lend themselves to measurement. These last two characteristics are absent among the Sustainable Development Goals.
Keywords: Development aims; Development policy; International organizations; Mednarodne organizacije; Napredek; OZN; Progress; Razvojna politika; Razvojni cilji